Non-aqueous electrolyte solution and battery
By adding silicon-based fluorophosphate compound to the electrolyte, a stable interface film is formed, which solves the problem of insufficient oxidation stability of ether solvents and improves the cycle stability and high temperature resistance of lithium batteries.
Patent Information
- Application Number
- CN202411742158.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The oxidation stability of ether solvents in high-voltage lithium batteries is insufficient, resulting in the high voltage stability of the electrolyte being unable to meet the demand.
By adding silicon-based fluorophosphate compound as an additive to the electrolyte, a high conductivity, rigidity and dense and stable interface film is formed, the direct oxidation of ether compounds is avoided, and the desolvation ability of lithium ions is changed, and solvent molecules are inhibited from being embedded in the negative electrode material.
It improves the cycle stability and high temperature resistance of lithium batteries, enhances the high voltage stability of electrolyte, reduces the internal resistance of the battery, and improves the overall performance of the battery.
Smart Images

Figure CN119674236A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular, relates to non-aqueous electrolytes and batteries. Background Art
[0002] High-voltage lithium batteries with high energy density are regarded as favorable competitors for the next generation of secondary battery systems, but they are also constrained by low cycle life and safety issues in practical applications. As the "blood" of the battery, the electrolyte plays a vital role in improving the battery's pressure resistance, cycle stability and safety. Ether solvents have relatively high reduction stability, can achieve high coulomb efficiency (95% to 99%), have a good inhibitory effect on the formation of lithium dendrites, and also have high lithium salt solubility and high lithium ion conductivity, so they have received widespread attention. However, the oxidation stability of ether solvents is usually difficult to meet the needs of high-voltage lithium batteries, so there is an urgent need to improve the high voltage stability of ether electrolytes. Summary of the invention
[0003] The present invention aims to solve the technical problem of improving the stability of a battery at least to a certain extent. To this end, one object of the present invention is to provide a non-aqueous electrolyte and a battery. The non-aqueous electrolyte is applied to a battery and exhibits high high voltage stability.
[0004] In a first aspect, an embodiment of the present application provides a non-aqueous electrolyte. According to an embodiment of the present application, the non-aqueous electrolyte includes: an additive and a first solvent and a second solvent; the additive includes a silicon-based fluorophosphate compound, and the silicon-based fluorophosphate compound is shown in Formula 1:
[0005]
[0006] Among them, R 1 , R 2 and R 3 Each independently includes H, F, C 1 -C 4 Alkyl, C 1 -C 4 Fluorinated alkyl, C 2 -C 4 The alkenyl group, C 2 -C 4 Fluoroalkenyl, C 2 -C 4 Alkynyl, C 5 -C 7 Cycloalkanes, R 4 Substituted phenyl and R 5 Any one of the substituted benzyl groups, R 1 , R 2 and R 3The first solvent comprises an ether compound; the second solvent comprises at least one of a carbonate compound, a carboxylate compound, a sulfone compound and a nitrile compound.
[0007] The present application adds silicon-based fluorophosphate compounds as electrolyte additives, utilizing the property of silicon-based fluorophosphate compounds that can form organic-inorganic interface films on the surfaces of positive and negative electrodes, and constructs an interface film that has high conductivity, rigidity, and dense stability. On the one hand, it avoids direct oxidation of ether compounds at the interface of positive electrode materials, and on the other hand, it can change the desolvation ability of lithium ions and inhibit the embedding of solvent molecules into the negative electrode material, thereby enabling high-voltage lithium batteries to exhibit excellent cycle stability and high temperature resistance.
[0008] In some embodiments of the present application, the ether compound includes at least one of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms.
[0009] In some embodiments of the present application, the chain ether compounds having 3 to 10 carbon atoms include ethyl ether, di(2,2,2-trifluoroethyl) ether, ethyl(2,2,2-trifluoroethyl) ether, ethyl n-propyl ether, ethyl(3-fluoro n-propyl) ether,(2,2,2-trifluoroethyl)(3,3,3-trifluoro n-propyl) ether, di(2,2,3,3,3-pentafluoro n-propyl) ether, dimethoxymethane, methoxyethoxymethane, methoxy(2-fluoroethoxy)methane, diethoxymethane, ethoxy(2-fluoroethoxy)methane, The cyclic ether compound having 3 to 6 carbon atoms includes any one of tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane and 1,4-dioxolane.
[0010] In some embodiments of the present application, the ether compound includes a fluorine-substituted ether compound.
[0011] In some embodiments of the present application, R 4 , R 5 Independent including F, C 1 -C 4 Alkyl, C 2 -C 4 The alkenyl group, C 2 -C 4 Alkynyl, C 1 -C 4 Fluorinated alkyl, C2 -C 4 Any one of the fluoroalkenyl groups.
[0012] In some embodiments of the present application, R 1 , R 2 , R 3 Each independently is C 1 -C 2 The alkyl and C 2 -C 3 Any one of the alkenyl groups; and / or, the R 4 and R 5 Each is independently F or methyl.
[0013] In some embodiments of the present application, the compound represented by Formula 1 includes at least one of the compounds represented by the following Formulas 1-1 to 1-22:
[0014] Compound represented by formula 1-1 Compound represented by formula 1-2 Compounds shown in formula 1-3 Compounds shown in formula 1-4 Compounds shown in formula 1-5 Compounds shown in formula 1-6 Compounds shown in formula 1-7 Compound represented by formula 1-8 Compounds shown in formula 1-9 Compound represented by formula 1-10 Compound represented by formula 1-11 Compounds shown in formula 1-12 Compounds shown in formula 1-13 Compounds shown in formula 1-14 Compound represented by formula 1-15 Compound represented by formula 1-16 Compound represented by formula 1-17 Compound represented by formula 1-18 Compound represented by formula 1-19 Compounds shown in formula 1-20 Compound represented by formula 1-21 Compound represented by formula 1-22
[0015] In some embodiments of the present application, at least one of the following is satisfied:
[0016] (i) the second solvent is a carbonate compound;
[0017] (ii) the first solvent is a combination of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms;
[0018] (iii) The first solvent is a combination of a fluorine-substituted ether compound and a non-fluorine-substituted ether compound.
[0019] In some embodiments of the present application, the non-aqueous electrolyte satisfies at least one of the following:
[0020] (a) The mass percentage of the additive in the electrolyte is 0.05% to 5.0%;
[0021] (b) the mass percentage of the first solvent in the electrolyte is 20% to 90%;
[0022] (c) The mass percentage of the second solvent in the electrolyte is 3% to 70%.
[0023] In some embodiments of the present application, an electrolyte salt is further included, and the electrolyte salt includes a lithium salt or a sodium salt; the electrolyte salt satisfies at least one of the following:
[0024] (a) Lithium salts include inorganic lithium salts and organic lithium salts;
[0025] Optionally, the organic lithium salt includes at least one of carboxylic acid lithium salts, sulfonic acid lithium salts, imide lithium salts, methylated lithium salts, boric acid lithium salts, lithium oxalate salts and fluorinated ester sulfonic acid lithium salts; the inorganic lithium salt includes at least one of lithium hexafluorophosphate and lithium perchlorate;
[0026] (b) sodium salts include at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bis(oxalatoborate), sodium difluorophosphate, sodium difluorooxalatophosphate, sodium tetrafluorooxalatophosphate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide;
[0027] (b) The mass percentage of the electrolyte salt in the electrolyte is 6% to 30%.
[0028] The second aspect of the present application provides a battery comprising the above-mentioned non-aqueous electrolyte.
[0029] The battery provided in the embodiment of the present application has good high-voltage stability. The battery contains the above-mentioned electrolyte, which enables the high-voltage system battery to exhibit excellent cycle stability and high temperature resistance.
[0030] In some embodiments of the present application, the battery includes a sodium secondary battery and a lithium secondary battery.
[0031] In some embodiments of the present application, the sodium secondary battery includes a positive electrode sheet, a negative electrode sheet and a separator; and satisfies at least one of the following:
[0032] (α) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, the positive electrode active material NaNi x Fe y M z O 2 、Na 3 V 2 (PO 4 ) 3 、Na 0.9 Mn 0.6 Fe 0.4 PO 4 , at least one of sodium ferric pyrophosphate and sodium ferrocyanide; wherein M comprises one or more of Co, Mn, Fe, Cu, x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1;
[0033] (β) the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer, the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes at least one of sodium metal, soft carbon, hard carbon, sodium titanate, and sodium alloy;
[0034] (γ) The separator includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
[0035] In some embodiments of the present application, the lithium secondary battery includes a positive electrode sheet, a negative electrode sheet and a separator; and satisfies at least one of the following:
[0036] (α) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes LiCoO 2 、LiMn 2 O 4 、LiMnO 2 , Li 2 MnO 4 、LiFePO 4 , Li 1+a Mn 1-x M x O 2 、LiCo 1-x M x O 2 、LiFe 1-x M x PO 4 , Li 2 Mn 1-x O 4 , M is selected from one or more of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1;
[0037] (β) The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer, and the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes at least one of metallic lithium, graphite, soft carbon, hard carbon, silicon, silicon oxide, silicon carbon composite and lithium titanate;
[0038] (γ) The separator includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
[0039] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0040] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0041] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0044] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0045] At present, ether solvents have relatively high reduction stability, can achieve high coulomb efficiency (95% to 99%), have a good inhibitory effect on the formation of lithium dendrites, and also have high lithium salt solubility and high lithium ion conductivity, so they have received widespread attention. However, the oxidation stability of ether solvents is usually difficult to meet the needs of high-voltage lithium batteries, so there is an urgent need to improve the high-voltage stability of ether electrolytes. In response to this problem, the available solutions are to use high-concentration electrolytes, local high-concentration electrolytes and weakly solvated electrolytes, but they will significantly reduce the conductivity of ether electrolytes. The present application uses silicon-based fluorophosphate compounds as electrolyte additives to improve the oxidation resistance of the electrolyte and improve the high-voltage stability. In addition, it is also beneficial to improve the problem of reduced conductivity of ether electrolytes.
[0046] Specifically, in a first aspect, an embodiment of the present application provides a non-aqueous electrolyte, including an additive and a first solvent; the additive includes a silicon-based fluorophosphate compound, and the silicon-based fluorophosphate compound is shown in Formula 1:
[0047]
[0048] Among them, R 1 , R 2 and R 3 Each independently includes H, F, C 1 -C 4 Alkyl, C 1 -C 4 Fluorinated alkyl, C 2 -C 4 The alkenyl group, C 2 -C 4 Fluoroalkenyl, C 2 -C 4 Alkynyl, C 5 -C 7 Cycloalkanes, R 4 Substituted phenyl and R 5 Any one of the substituted benzyl groups, R 1 , R 2 and R 3 The first solvent comprises an ether compound; the second solvent comprises at least one of a carbonate compound, a carboxylate compound, a sulfone compound and a nitrile compound.
[0049] The embodiments of the present application add silicon-based fluorophosphate compounds as electrolyte additives, utilizing the property of silicon-based fluorophosphate compounds that can form organic-inorganic interface films on the surfaces of the positive and negative electrodes, and construct an interface film that has high conductivity, rigidity, and dense stability. On the one hand, it avoids the direct oxidation of ether compounds at the interface of the positive electrode material, as well as the impedance increase and high-temperature gas production problems caused by the second solvent. On the other hand, it can change the desolvation ability of lithium ions and inhibit the embedding of solvent molecules into the negative electrode material, thereby enabling high-voltage lithium batteries to exhibit excellent cycle stability and high-temperature resistance.
[0050] Specifically, in the embodiments of the present application, the ether compound used as the first solvent has the advantages of a low melting point, low viscosity and strong solvation ability for lithium ions, which gives the electrolyte a higher lithium salt solubility ability and a higher ionic conductivity, which is beneficial to reducing the electrolyte impedance and giving the lithium-ion battery excellent low temperature and fast charging performance. At the same time, the ether compound has a high reduction stability and can achieve preferential reduction of anions in additives or lithium salts at the negative electrode interface. The resulting interface film reduces the irreversible reduction decomposition of the electrolyte on the negative electrode side, inhibits the generation of lithium dendrites on the negative electrode side, and significantly improves the battery's cycle coulomb efficiency. However, ether compounds are difficult to be used alone in lithium-ion batteries because ether compounds have a stronger interaction with lithium ions and are not easily separated from lithium ions during the charging process. They will be co-embedded in the negative electrode material along with the lithium ions, resulting in volume expansion and irreversible peeling due to changes in the negative electrode structure. At the same time, ether compounds have low oxidative stability and will undergo severe oxidation at high voltages (>4.0V). They cannot build a stable interface film to protect the electrolyte, resulting in continuous oxidative decomposition of the electrolyte components, and the generated acidic substances will corrode and destroy the structure of the positive electrode material and cause the dissolution of transition metals, resulting in rapid decay of the battery capacity.
[0051] In order to alleviate the negative impact of the use of ether compounds alone, a second solvent can usually be introduced to construct a co-solvent system. The introduced second solvent mainly includes carbonate compounds, carboxylic acid ester compounds, sulfone compounds and nitrile compounds. Among them, carbonate compounds have a suitable temperature application range and oxidation stability, a high dielectric constant, good compatibility with positive and negative electrode materials, can construct an interface film on the surface of the positive and negative electrodes and have good stability, can inhibit the solvent molecules from being embedded in the negative electrode structure, and alleviate the volume expansion caused by the exfoliation of the negative electrode graphite. However, the interface film constructed by them contains more Li 2 O and Li 2 CO 3 The components that increase the interfacial impedance may lead to an increase in the battery impedance, and the acidic substances produced by the oxidation of the first solvent at the positive electrode will consume the Li in the interfacial film during the long cycle process. 2 O and Li 2 CO3 Components such as sulfone lead to gas production in the battery, which results in only limited improvement in cycle performance; sulfone compounds have good high temperature and high pressure stability, high dielectric constant, and the stable and dense interface film constructed can inhibit the high-pressure oxidation problem of the first solvent, among which Li-rich 2 S. Li 2 SO 3 Components such as the above can also improve the interfacial conductivity, but their compatibility with the negative electrode is poor, and the problem of negative electrode volume expansion caused by the first solvent cannot be solved well; the cyanide group in the nitrile compound has a strong interaction with lithium ions, has a strong solvation ability, has a good film-forming property, inhibits the solvation structure from being embedded in the graphite negative electrode, and the constructed interface film has good flexibility and corrosion resistance, can better inhibit volume expansion and acidic substances from corroding the interface film, and has good high-temperature storage performance, but the thickness of the constructed interface film is relatively thick, which will affect the embedding and extraction of lithium ions, resulting in increased impedance, affecting the room temperature cycle performance of the battery.
[0052] In order to solve the problems of low oxidation stability of ether compounds, embedding of solvents into the negative electrode, increased impedance of the second solvent, and high-temperature gas production, which lead to poor high temperature and cycle performance of the battery, silicon-based fluorophosphate compounds are used as additives in the electrolyte to improve the cycle capacity retention and high-temperature storage stability of the battery under high voltage conditions. Silicon-based fluorophosphate compounds have a low redox potential, and form stable CEI films (abbreviation for "Cathode Electrolyte Interphase") and SEI films (abbreviation for "Solid Electrolyte Interphase") on the surfaces of the positive and negative electrodes, respectively, producing a stable protective effect on the positive electrode material, negative electrode material and electrolyte. For the positive electrode, the Si-O bond in the silicon-based fluorophosphate compound has a high reactivity, and is oxidized and decomposed on the positive electrode surface before the solvent molecules, and combines with the lithium ions in the electrolyte to produce lithium fluoride, lithium phosphate, and Li x PO y F zInorganic lithium salts and dense organic polysiloxanes that improve lithium ion transmission are used to generate an organic-inorganic protective layer that can inhibit side reactions at the interface, avoid oxidative decomposition of solvent molecules and loosening and deterioration of interface film components due to the production of by-products, and achieve high oxidative stability of ether solvents. It has a high conductivity, rigidity and dense and stable interface film, which on the one hand avoids direct contact between ether compounds and positive electrode materials, and on the other hand, P=O in fluorinated lithium phosphate salts and Si-O in polysiloxanes have a good stabilizing effect on positive electrode metal ions, which has a good protective effect on ether solvents while also inhibiting the dissolution of transition metals, thereby having a good improvement effect on high-temperature storage stability and cycle stability under high voltage conditions. For the negative electrode, silicon-containing compounds can form polymers as a skeleton structure attached to the negative electrode surface to maintain the stability of the interface film. The P=O in the fluorinated lithium phosphate in the interface film component has a good binding effect on lithium ions, which is beneficial to changing the desolvation ability of lithium ions. The dense and stable organic-inorganic interface film inhibits the embedding of solvent molecules into the negative electrode material, which is ultimately beneficial to the long-term stable cycle of lithium-ion batteries.
[0053] In this specific example, R 1 , R 2 , R 3 Each independently selected from H, F, C 1 -C 4 Alkyl, C 1 -C 4 Fluorinated alkyl, C 2 -C 4 The alkenyl group, C 2 -C 4 Fluoroalkenyl, C 2 -C 4 Any one of substituted alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl. 1 -C 4 The alkyl group includes one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; 1 -C 4 The fluorinated alkyl group may be a partially fluorinated C 1 -C 4 The alkyl group may also be a C 1 -C 4 Of which, C 2 -C 4 The alkenyl groups include vinyl, propenyl (CH 2 =CHCH 2 -), 1-propenyl (CH 3 CH=CH-), 2-propenyl (CH 2 =C(CH 3)-), butenyl (CH 2 =CHCH 2 CH 2 -), isobutylene (CH 2 =CHCH(CH 3 )-), 1-methylpropenyl (CH 2 =C(CH 3 ) 2 -) and 2-methylpropenyl (CH 2 =CHC(CH 3 ) 2 -); C 2 -C 4 The fluoroalkenyl group may be a partially fluorinated C 2 -C 4 The alkenyl group can also be a C 2 -C 4 Of which, C 2 -C 4 Alkynyl groups include ethynyl, 1-propynyl (CH 3 C≡C-), 2-propynyl (HC≡CCCH 3 ), 3-propynyl (H 2 CCC≡C-), 1-butynyl (CH 3 CH 2 C≡C-), 2-butynyl (CH 3 CH 2 C≡CH), 3-butynyl (CH 3 C≡CCH 2 -), 4-butynyl (HC≡CCH 2 CH 2 -), 1-methyl-2-propynyl (CH 3 C≡CCH 3 )、2-methyl-1-propynyl(HC≡CC(CH 3 ) 2 )
[0054] As an example, carbonate compounds include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), (fluoromethyl) methyl carbonate, (difluoromethyl) methyl carbonate, (trifluoromethyl) methyl carbonate, bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, (2-fluoroethyl) methyl carbonate, (2,2-difluoroethyl) methyl carbonate, (2,2,2-trifluoroethyl) methyl carbonate, (2-fluoroethyl) fluoromethyl carbonate ester, (2-fluoroethyl) difluoromethyl carbonate, (2,2-difluoroethyl) fluoromethyl carbonate, (ethyl) fluoromethyl carbonate, (ethyl) difluoromethyl carbonate, (ethyl) trifluoromethyl carbonate, (2-fluoroethyl) ethyl carbonate, (2,2-difluoroethyl) ethyl carbonate, (2,2,2-trifluoroethyl) ethyl carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate and trifluoromethylethylene carbonate.
[0055] As an example, the carboxylate compounds include linear carboxylates and cyclic carboxylates, the linear carboxylates include one or more of methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, tert-butyl propionate, methyl butyrate, ethyl butyrate, n-propyl butyrate, isopropyl butyrate, methyl isobutyrate, ethyl isobutyrate, n-propyl isobutyrate, isopropyl isobutyrate, and the cyclic carboxylates include at least one of γ-butyrolactone, γ-valerolactone, γ-caprolactone and ε-caprolactone.
[0056] As an example, the sulfone compounds include cyclic sulfones and chain sulfones, the chain sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, n-propyl methyl sulfone, isopropyl methyl sulfone, n-butyl methyl sulfone, tert-butyl methyl sulfone, monofluoromethyl methyl sulfone, difluoromethyl methyl sulfone, trifluoromethyl methyl sulfone, monofluoroethyl methyl sulfone, difluoroethyl methyl sulfone, trifluoroethyl methyl sulfone, pentafluoroethyl methyl sulfone, ethyl monofluoromethyl sulfone, ethyl difluoromethyl sulfone, ethyl trifluoromethyl sulfone, ethyl trifluoroethyl sulfone, ethyl pentafluoroethyl sulfone, trifluoromethyl n-propyl sulfone, trifluoromethyl isopropyl sulfone, trifluoroethyl n-butyl sulfone, trifluoroethyl tert-butyl sulfone, trifluoromethyl n-butyl sulfone, one or more of trifluoromethyl tert-butyl sulfone; the cyclic sulfones are mainly sulfolane and sulfolane derivatives, including sulfolane, 2-methylsulfolane, 3-methylsulfolane, 2-fluorosulfolane, 3-fluorosulfolane Sulfone, 2,2-difluorosulfolane, 2,3-difluorosulfolane, 2,4-difluorosulfolane, 2,5-difluorosulfolane, 3,4-difluorosulfolane, 2-fluoro-3-methylsulfolane, 2-fluoro-2-methylsulfolane, 3-fluoro-3-methylsulfolane, 3-fluoro-2-methylsulfolane, 4-fluoro-3-methylsulfolane, 4-fluoro-2-methylsulfolane, 5-fluoro-3-methylsulfolane, 5 -At least one of fluoro-2-methyl sulfolane, 2-fluoromethyl sulfolane, 3-fluoromethyl sulfolane, 2-difluoromethyl sulfolane, 3-difluoromethyl sulfolane, 2-trifluoromethyl sulfolane, 3-trifluoromethyl sulfolane, 2-fluoro-3-(trifluoromethyl) sulfolane, 3-fluoro-3-(trifluoromethyl) sulfolane, 4-fluoro-3-(trifluoromethyl) sulfolane and 5-fluoro-3-(trifluoromethyl) sulfolane.
[0057] As an example, nitrile compounds include compounds having 1 cyano group, 2 cyano groups and 3 cyano groups. The compounds having one cyano group include acetonitrile, propionitrile, butyronitrile, isobutyronitrile, valeronitrile, isovaleronitrile, dodecanenitrile, crotononitrile and 3-methylcrotononitrile; the compounds having two cyano groups include malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, sebacatenitrile, undecane dinitrile and dodecane dinitrile; the compounds having three nitrile groups include at least one of 1,2,3-tris(2-cyanoethoxy)propane and tris(2-cyanoethyl)amine.
[0058] In some embodiments of the present application, the ether compound includes at least one of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms.
[0059] In the embodiments of the present application, ether compounds have the characteristics of low melting point, low viscosity, and stronger lithium ion solvation ability. The use of ether compounds can improve the conductivity of the electrolyte and lower the electrode overpotential. It has high reduction stability at the negative electrode, reduces the irreversible reduction decomposition of the electrolyte on the negative electrode side, and is beneficial to the reduction of additives to form an interface film with more inorganic components, which can improve the interface stability and help reduce the electrolyte impedance, thereby improving the high temperature storage and cycle performance of the battery.
[0060] In the embodiments of the present application, the first solvent may be a chain ether compound having 3 to 10 carbon atoms, or a cyclic ether compound having 3 to 6 carbon atoms, or a combination of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms.
[0061] In some embodiments of the present application, the chain ether compound having 3 to 10 carbon atoms includes at least one of ethyl ether, di(2,2,2-trifluoroethyl) ether, ethyl(2,2,2-trifluoroethyl) ether, ethyl n-propyl ether, ethyl(3-fluoro-n-propyl) ether, (2,2,2-trifluoroethyl)(3,3,3-trifluoro-n-propyl) ether, di(2,2,3,3,3-pentafluoro-n-propyl) ether, dimethoxymethane, methoxyethoxymethane, methoxy(2-fluoroethoxy)methane, diethoxymethane, ethoxy(2-fluoroethoxy)methane, (2,2,2-trifluoroethoxy)(1,1,2,2-tetrafluoroethoxy)ethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, ethylene glycol dimethyl ether and diethylene glycol dimethyl ether;
[0062] And / or, the cyclic ether compound having 3 to 6 carbon atoms includes any one of tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane and 1,4-dioxolane.
[0063] In the embodiments of the present application, these ether compounds have the characteristics of low melting point and low viscosity, which are beneficial to reduce the impedance of the electrolyte and improve the high-temperature storage and cycle performance of the battery.
[0064] In some embodiments of the present application, the ether compound includes a fluorine-substituted ether compound.
[0065] The fluorine-substituted ether compound refers to an ether compound in which any hydrogen atom in the molecular structure can be replaced by fluorine.
[0066] In the embodiments of the present application, by replacing hydrogen atoms in the molecular structure of the ether compound with fluorine, the LUMO and HOMO energy levels of the compound can be reduced based on the strong electronegativity and weak polarity of the fluorine atom, thereby improving the oxidation stability of the ether compound. At the same time, LiF produced by the decomposition of the fluorinated ether is an important component of the positive electrode CEI film, and has good mechanical stability and a wide electrochemical window. The interface film rich in LiF is beneficial to improving the oxidizability of the ether compound and improving the cycle stability of the battery.
[0067] In some embodiments of the present application, R 4 , R 5 Independent including F, C 1 -C 4 Alkyl, C 2 -C 4 The alkenyl group, C 2 -C 4 Alkynyl, C 1 -C 4 Fluorinated alkyl, C 2 -C 4 Any one of the fluoroalkenyl groups.
[0068] Among them, C 1 -C 4 The alkyl group includes one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; 1 -C 4 The fluorinated alkyl group may be a partially fluorinated C 1 -C 4 The alkyl group may also be a C 1 -C 4 Of which, C 2 -C 4 The alkenyl groups include vinyl, propenyl (CH 2 =CHCH 2 -), 1-propenyl (CH 3 CH=CH-), 2-propenyl (CH 2 =C(CH 3 )-), butenyl (CH 2 =CHCH 2 CH 2 -), isobutylene (CH 2 =CHCH(CH 3 )-), 1-methylpropenyl (CH 2 =C(CH 3 ) 2 -) and 2-methylpropenyl (CH 2 =CHC(CH 3 ) 2-); C 2 -C 4 The fluoroalkenyl group may be a partially fluorinated C 2 -C 4 The alkenyl group can also be a C 2 -C 4 Of which, C 2 -C 4 Alkynyl groups include ethynyl, 1-propynyl (CH 3 C≡C-), 2-propynyl (HC≡CCCH 3 ), 3-propynyl (H 2 CCC≡C-), 1-butynyl (CH 3 CH 2 C≡C-), 2-butynyl (CH 3 CH 2 C≡CH), 3-butynyl (CH 3 C≡CCH 2 -), 4-butynyl (HC≡CCH 2 CH 2 -), 1-methyl-2-propynyl (CH 3 C≡CCH 3 )、2-methyl-1-propynyl(HC≡CC(CH 3 ) 2 )
[0069] In some embodiments of the present application, R 1 , R 2 , R 3 Each independently is C 1 -C 2 The alkyl and C 2 -C 3 Any one of the alkenyl groups; and / or, R 4 and R 5 Each is independently F or methyl.
[0070] In the present application, R 1 , R 2 , R 3 Each independently is C 1 -C 2 The alkyl and C 2 -C 3 Any of the alkenyl groups of the present invention, these groups have shorter carbon chains, which are conducive to polymerization to form polysiloxane, while avoiding the increase of interface film thickness and impedance.
[0071] In the present application, R 4 and R 5Each is independently F or methyl, and the carbon chain of the substituent is shorter, which is conducive to further polymerization and avoids the increase of the thickness of the interface film.
[0072] In some embodiments of the present application, the compound represented by Formula 1 includes at least one of the compounds represented by the following Formulas 1-1 to 1-22:
[0073] Compound represented by formula 1-1 Compound represented by formula 1-2 Compounds shown in formula 1-3 Compounds shown in formula 1-4 Compounds shown in formula 1-5 Compounds shown in formula 1-6 Compounds shown in formula 1-7 Compound represented by formula 1-8 Compounds shown in formula 1-9 Compound represented by formula 1-10 Compound represented by formula 1-11 Compounds shown in formula 1-12 Compounds shown in formula 1-13 Compounds shown in formula 1-14 Compound represented by formula 1-15 Compound represented by formula 1-16 Compound represented by formula 1-17 Compound represented by formula 1-18 Compound represented by formula 1-19 Compounds shown in formula 1-20 Compound represented by formula 1-21 Compound represented by formula 1-22
[0074] In some embodiments of the present application, at least one of the following is satisfied:
[0075] (i) the second solvent is a carbonate compound;
[0076] (ii) the first solvent is a combination of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms;
[0077] (iii) The first solvent is a combination of a fluorine-substituted ether compound and a non-fluorine-substituted ether compound.
[0078] In the embodiment of the present application, carbonate compounds can be selected as the second solvent. Carbonate compounds have a suitable temperature application range and oxidation stability, have a high dielectric constant, have good compatibility with positive and negative electrode materials, can construct an interface film on the surface of the positive and negative electrodes and have good stability, can inhibit the embedding of solvent molecules into the negative electrode structure, and alleviate the volume expansion effect caused by the exfoliation of negative electrode graphite.
[0079] In the embodiment of the present application, a combination of a chain ether compound with 3 to 10 carbon atoms and a cyclic ether compound with 3 to 6 carbon atoms can be selected as the first solvent. Compared with the first solvent, the cyclic ether has weaker solvation energy and weaker ability to snatch lithium ions from lithium salt anions. The combination of the chain ether and the cyclic ether is beneficial for the anions to combine with the lithium ions to form polymers, alleviates the secondary decomposition of the electrolyte components on the positive electrode side, and also contributes to the formation of inorganic components on the negative electrode side, thereby improving the electrode decomposition stability.
[0080] In the embodiment of the present application, a combination of fluorine-substituted ether compounds and non-fluorine-substituted ether compounds can be selected as the first solvent. Using non-fluorine-substituted solvent as the main solvent and adding fluorine-substituted solvent as the diluent to construct a local high-concentration electrolyte can produce a unique solvation structure, reduce free ether and thus reduce the HOMO energy level of the system, and the inner solvation shell contains more lithium salt anions, which also promotes the construction of the electrode interface layer.
[0081] In some embodiments of the present application, the non-aqueous electrolyte satisfies at least one of the following:
[0082] (a) the mass percentage of the additive in the electrolyte is 0.05% to 5.0%;
[0083] (b) the mass percentage of the first solvent in the electrolyte is 20% to 90%;
[0084] (c) The mass percentage of the second solvent in the electrolyte is 3% to 70%.
[0085] In the embodiment of the present application, the mass percentage of the additive in the electrolyte meets the above conditions, which is beneficial to improve the high-voltage stability of the battery, improve the overall battery performance, and at the same time help to avoid increasing the thickness of the interface film to increase the internal resistance, and help to avoid combining with too much lithium salt to consume too much lithium salt, resulting in capacity loss. In a specific example, the mass percentage of the silicon-based fluorophosphate compound in the electrolyte is 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, etc. Further, the mass percentage of the additive in the electrolyte is 0.5% to 2.5%.
[0086] In the embodiment of the present application, the mass percentage of the first solvent in the electrolyte meets the above conditions, which is beneficial to improve the high-voltage stability of the battery and ensure the dissolution of sufficient lithium salt. In a specific example, the mass percentage of the first solvent in the electrolyte is 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52% %, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, etc. Further, the mass percentage of the first solvent in the electrolyte is 52% to 60%, and further, the mass percentage of the first solvent in the electrolyte is 52% to 57.47%.
[0087] In the embodiment of the present application, the mass percentage of the second solvent in the electrolyte satisfies the above conditions. In the specific example, the mass percentage of the second solvent in the electrolyte is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 31%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 620%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% , 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% and so on.
[0088] In some embodiments of the present application, the non-aqueous electrolyte further includes an electrolyte salt, the electrolyte salt includes a lithium salt or a sodium salt; the electrolyte salt satisfies at least one of the following:
[0089] (a) Lithium salts include inorganic lithium salts and organic lithium salts;
[0090] Optionally, the organic lithium salt includes at least one of carboxylic acid lithium salts, sulfonic acid lithium salts, imide lithium salts, methylated lithium salts, boric acid lithium salts, lithium oxalate salts and fluorinated ester sulfonic acid lithium salts; the inorganic lithium salt includes at least one of lithium hexafluorophosphate and lithium perchlorate;
[0091] (b) sodium salts include at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bis(oxalatoborate), sodium difluorophosphate, sodium difluorooxalatophosphate, sodium tetrafluorooxalatophosphate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide;
[0092] (b) The mass percentage of the electrolyte salt in the electrolyte is 6% to 30%.
[0093] Those skilled in the art can select the lithium salt or sodium salt used in the art according to actual needs.
[0094] In some embodiments of the present application, the mass percentage of the electrolyte salt in the electrolyte is 6% to 30%. In specific examples, the mass percentage of the electrolyte salt in the electrolyte is 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28, 29%, 30%, etc.
[0095] Furthermore, the mass percentage of the electrolyte salt in the electrolyte is 8% to 12.5%.
[0096] A second aspect of an embodiment of the present application provides a battery comprising the above-mentioned non-aqueous electrolyte.
[0097] The battery provided in the embodiment of the present application has good high-voltage stability. The battery contains the above-mentioned electrolyte, which enables the high-voltage system battery to exhibit excellent cycle stability and high temperature resistance.
[0098] In some embodiments, the battery includes a sodium secondary battery and a lithium secondary battery.
[0099] In some embodiments, the sodium secondary battery includes a positive electrode sheet, a negative electrode sheet, and a separator; and satisfies at least one of the following:
[0100] (α) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer includes a positive electrode active material, wherein the positive electrode active material NaNi x Fe y M z O 2 、Na 3 V 2 (PO 4 ) 3 、Na0.9 Mn 0.6 Fe 0.4 PO 4 , at least one of sodium ferric pyrophosphate and sodium ferrocyanide; wherein M comprises one or more of Co, Mn, Fe, Cu, x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1;
[0101] (β) The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of sodium metal, soft carbon, hard carbon, sodium titanate, and sodium alloy;
[0102] (γ) The diaphragm includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
[0103] Furthermore, in the sodium alloy, the metal that forms an alloy with sodium may include one or more of potassium, aluminum, copper, and molybdenum.
[0104] In some embodiments, the lithium secondary battery includes a positive electrode sheet, a negative electrode sheet, and a separator; and satisfies at least one of the following:
[0105] (a) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes LiCoO 2 、LiMn 2 O 4 、LiMnO 2 , Li 2 MnO 4 、LiFePO 4 , Li 1+a Mn 1-x M x O 2 、LiCo 1-x M x O 2 、LiFe 1-x M x PO 4 , Li 2 Mn 1-x O 4 , M is selected from one or more of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1;
[0106] (β) The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of metallic lithium, graphite, soft carbon, hard carbon, silicon, silicon oxide, silicon carbon composite and lithium titanate;
[0107] (γ) The diaphragm includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
[0108] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0109]
Silicon-based fluorophosphate compounds
[0110] 1. The examples using silicon-based fluorophosphate compounds are as follows:
[0111] Compound represented by formula 1 CAS number: 2708941-25-5, referred to as compound 1. Compound represented by formula 2 CAS number: 4414-25-9, referred to as compound 2.
[0112] Compound represented by formula 3 CAS number: 13683-39-1, referred to as compound 3. The compound shown in formula 4 CAS number: 4414-27-1, referred to as compound 4. Compound represented by formula 5 CAS number: 4414-26-0, referred to as compound 5.
[0113] Compound represented by formula 6 CAS number: 4480-02-8, referred to as compound 6. Compound represented by formula 7 CAS number: 2577172-95-1, referred to as compound 7.
[0114] Compound represented by formula 8 CAS number: 13683-40-4, referred to as compound 8. Compound represented by formula 9 CAS number: 2577172-93-9, referred to as compound 9. Compound represented by formula 10 CAS number: 2708941-27-7, referred to as compound 10.
[0115] Compound represented by formula 11 CAS number: 2287283-36-5, referred to as compound 11.
[0116] Compound represented by formula 12 CAS number: 6231-57-8, referred to as compound 12.
[0117] Compound represented by formula 13 CAS number: 1386-54-9, referred to as compound 13.
[0118] Compound represented by formula 14 CAS number: 2708941-26-6, referred to as compound 14.
[0119] Compound represented by formula 15 CAS number: 6231-58-9, referred to as compound 15.
[0120] Compound represented by formula 16 CAS number: 6231-59-0, referred to as compound 16.
[0121] Compound represented by formula 17 CAS number: 2577172-94-0, referred to as compound 17.
[0122] Compound represented by formula 18 Referred to as Compound 18.
[0123] Compound represented by formula 19 Referred to as compound 19.
[0124] Compound represented by formula 20 Referred to as Compound 20.
[0125] Compound represented by formula 21 Referred to as Compound 21.
[0126] Compound represented by formula 22 Referred to as compound 22.
[0127] 2. Compounds 18-22 Compounds 18 to 22 were prepared according to the preparation method of Example 14 in patent CN114728992A. Specifically, the raw materials shown below were used to replace chlorodimethylphenylsilane in the reference document.
[0128] Compound 18 The raw material chlorosilane is trivinyl chlorosilane (CAS No.: 1871-21-2). The raw material chlorosilane is dimethylacetylbutylchlorosilane (CAS No.: 2069196-19-4).
[0129] Compound 20 The raw material chlorosilane is dimethyl (trifluoropropylene) chlorosilane (CAS No.: 89705-02-2).
[0130] Compound 21 The raw material chlorosilane is tris(pentafluoroethyl)chlorosilane (CAS No.: 1620665-21-5).
[0131] Compound 22 The raw material chlorosilane is dimethyl (p-methylbenzyl) chlorosilane (CAS No.: 1833-28-9).
[0132]
Preparation and performance testing of lithium-ion batteries
[0133] Example 1
[0134] Preparation of electrolyte: The electrolyte was prepared with the following components according to mass fraction: 12.5% LiPF 6 , non-aqueous organic solvent 4-methyl-1,3-diepoxypentane is 35%, 1,2-dimethoxyethane is 21.5%, diethyl carbonate is 30%, and the compound represented by formula 1-2 is 1.0%.
[0135] Preparation of positive electrode: LiNi 0.5 Co 0.2 Mn 0.3 O 2 The positive electrode material (NCM523), the conductive agent SuperP (conductive carbon black), the conductive agent CNT (carbon nanotube), and the binder PVDF (polyvinylidene fluoride) were mixed uniformly in a mass ratio of 96.3:2:0.5:1.2, and vacuum stirred until the fluidity was uniform to obtain a positive electrode slurry; then, the positive electrode slurry was evenly coated on the front and back sides of the aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and vacuum dried at 85°C for 12 hours. After welding the pole ears, the surface density was 33 mg / cm 2 The positive electrode.
[0136] Preparation of negative electrode sheet: Graphite negative electrode material, conductive agent Super P (conductive carbon black), thickener CMC (sodium carboxymethyl cellulose), and adhesive SBR (styrene-butadiene rubber latex) are fully mixed into a uniform slurry at a mass ratio of 95:1.5:1.5:2. After coating on both sides of the copper foil, it is dried at 85°C, and then cold pressed, trimmed, cut, and stripped. Finally, it is dried at 85°C under vacuum conditions for 12 hours. The electrode ear is welded to obtain a surface density of 19.3 mg / cm 2 The negative electrode.
[0137] Diaphragm: A 9 μm thick polyethylene porous polymer film is used as the substrate, and a 2 μm adhesive coating PVDF (polyvinylidene fluoride) is coated on both sides of the substrate.
[0138] Lithium-ion battery preparation:
[0139] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and wound into a bare cell with a theoretical capacity of 1600 mAh. The bare cell is placed in an outer packaging aluminum foil and vacuum-baked at 75°C for 10 hours before injecting the electrolyte. After vacuum packaging, standing, formation, aging, capacity division and other processes, the lithium-ion battery is completed.
[0140] Example 2-49
[0141] The method provided in Example 1 is adopted, and the components and contents are shown in Tables 1 to 6.
[0142] Comparative Examples 1-3
[0143] The method provided in Example 1 is adopted, and the components and contents are shown in Table 6.
[0144] Performance Testing
[0145] 1. Test method of NCM523-graphite battery system.
[0146] 1.25℃ normal temperature cycle test:
[0147] At 25°C, charge at a constant current of 1.0C to 4.35V, charge at a constant voltage of 4.35V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.75V; repeat the charge and discharge steps for 1000 cycles, test and record the discharge capacity of the 1000th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0148] 2.45℃ high temperature cycle test:
[0149] At 45°C, charge at a constant current of 1.0C to 4.35V, charge at a constant voltage of 4.35V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.75V; repeat the charge and discharge steps for 800 cycles, and test and record the discharge capacity of the 800th cycle and the first cycle, and divide the two to get the capacity retention rate.
[0150] 3.60℃ high temperature 30 days storage test:
[0151] At 25°C, the battery was charged to 4.35V at 1.0C constant current, and charged to a cut-off current of 0.05C at 4.35V constant voltage. The battery was then discharged to 2.75V at 1.0C constant current. The discharge capacity was recorded as C. 1 At 25°C, the battery was charged to 4.35V at 1.0C constant current, and charged to a cut-off current of 0.05C at 4.35V constant voltage. The battery was then transferred to 60°C and left for 30 days. The battery was then discharged to 2.75V at 1.0C constant current. The discharge capacity was recorded as C. 2 , 60℃ storage for 30 days capacity retention rate = C 2 / C1 *100%.
[0152] 4. High temperature DCIR (abbreviation for “Direct Current Internal Resistance”) test:
[0153] The lithium-ion battery was charged at 1.0C constant current to 4.35V at 25°C, and charged at 4.35V constant voltage to a cut-off current of 0.05C. The battery was then discharged at 1.0C constant current for 30min. After standing for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 1 The battery that has completed the 60℃ high temperature 30-day storage test was charged to 4.35V at 1.0C constant current at 25℃, and charged to a cut-off current of 0.05C at a constant voltage of 4.35V. The battery was then discharged at a constant current of 1.0C for 30 minutes. After being left for 1 hour, it was discharged at a constant current of 2.0C for 10 seconds. The DCIR of the battery at 50% SOC was calculated and recorded as D 2 Battery impedance change rate = D 2 / D 1 *100%.
[0154] 5. High temperature expansion test:
[0155] The lithium-ion battery was charged at 25°C at a constant current of 1.0C to 4.35V, and then at a constant voltage of 4.35V to a cut-off current of 0.05C. The initial thickness of the lithium-ion battery was measured and recorded as T 1 Then store at 60℃ for 30d, test the thickness of lithium-ion battery at 60℃, and record the value as T 2 . Battery expansion rate (%) = (T 2 -T 1 ) / T 1 ×100%.
[0156] 2. Test methods for NCM811-graphite battery system
[0157] 1.25℃ normal temperature cycle test:
[0158] At 25°C, charge the battery to 4.2V at a constant current of 1.0C, charge it to a cut-off current of 0.05C at a constant voltage of 4.2V, and then discharge it to 3.0V at a constant current of 1.0C. Repeat the charge and discharge steps for 1000 cycles, and record the discharge capacity of the 1000th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0159] 2.45℃ high temperature cycle test:
[0160] At 45°C, charge at a constant current of 1.0C to 4.2V, charge at a constant voltage of 4.2V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 3.0V; repeat the charge and discharge steps for 800 cycles, test and record the discharge capacity of the 800th cycle and the first cycle, and divide the two to get the capacity retention rate.
[0161] 3.60℃ high temperature 30 days storage test:
[0162] At 25°C, the battery was charged to 4.2V at 1.0C constant current, charged to a cut-off current of 0.05C at 4.2V constant voltage, and then discharged to 3.0V at 1.0C constant current. The discharge capacity is recorded as C 1 At 25°C, the battery was charged to 4.2V at 1.0C constant current, and charged to a cut-off current of 0.05C at 4.2V constant voltage. The battery was then transferred to 60°C and left for 30 days. The battery was then discharged to 3.0V at 1.0C constant current. The discharge capacity was recorded as C. 2 , 60℃ storage for 30 days capacity retention rate = C 2 / C 1 *100%.
[0163] 4. High temperature DCIR (abbreviation for “Direct Current Internal Resistance”) test:
[0164] The lithium-ion battery was charged at 1.0C constant current to 4.2V at 25°C, and charged at 4.2V constant voltage to a cut-off current of 0.05C. The battery was then discharged at 1.0C constant current for 30min. After standing for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 1 The battery that has completed the 60℃ high temperature 30-day storage test was charged to 4.2V at 1.0C constant current at 25℃, and charged to a cut-off current of 0.05C at 4.2V constant voltage. The battery was then discharged at 1.0C constant current for 30min. After being left for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 2 Battery impedance change rate = D 2 / D 1 *100%.
[0165] 5. High temperature expansion test:
[0166] The lithium-ion battery is charged at 25°C at a constant current of 1.0C to 4.2V, and then at a constant voltage of 4.2V to a cut-off current of 0.05C. The initial thickness of the lithium-ion battery is measured and recorded as T 1 Then store at 60℃ for 30d, test the thickness of lithium-ion battery at 60℃, and record the value as T 2. Battery expansion rate (%) = (T 2 -T 1 ) / T 1 ×100%.
[0167]
Preparation and performance testing of lithium metal batteries
[0168] Embodiment 50
[0169] Preparation of electrolyte: The electrolyte is prepared with the following components according to mass fraction: 12.5% LiPF 6 , non-aqueous organic solvent 4-methyl-1,3-diepoxypentane is 35%, 1,2-dimethoxyethane is 21.5%, dimethyl carbonate is 30%, and the compound represented by formula 1-2 is 1.0%.
[0170] Positive electrode preparation: LiNi 0.8 Co 0.1 Mn 0.1 O 2 The positive electrode active material (NCM811), the conductive agent SuperP (conductive carbon black), the conductive agent CNT (carbon nanotube), and the binder PVDF (polyvinylidene fluoride) were mixed uniformly in a mass ratio of 96.3:2:0.5:1.2, and vacuum stirred until the fluidity was uniform to obtain a positive electrode slurry; then, the positive electrode slurry was evenly coated on the front and back sides of the aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and vacuum dried at 85°C for 12 hours. After welding the pole ears, the surface density was 33 mg / cm 2 The positive electrode.
[0171] Preparation of negative electrode sheet: 6μm thick copper foil is purchased from the market, and a 20μm thick lithium layer is coated on both sides. The copper-lithium composite strip is trimmed, cut into pieces, and stripped, and then the pole ears are welded to make a lithium metal negative electrode sheet that meets the requirements.
[0172] Diaphragm: A 9 μm thick polyethylene porous polymer film is used as the substrate, and a 2 μm adhesive coating PVDF (polyvinylidene fluoride) is coated on both sides of the substrate.
[0173] Preparation of lithium metal batteries:
[0174] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and wound into a bare cell with a theoretical capacity of 1400 mAh. The bare cell is placed in an outer packaging aluminum foil and then injected with the electrolyte. After vacuum packaging, standing, formation, aging, capacity division and other processes, the lithium metal battery is completed.
[0175] NCM811-Test methods for lithium metal battery systems
[0176] 1.25℃ normal temperature cycle test:
[0177] At 25°C, charge at a constant current of 0.33C to 0.3V, charge at a constant voltage of 4.2V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 0.3C to 3.0V; repeat the charge and discharge steps for 600 cycles, and test and record the discharge capacity of the 600th cycle and the first cycle, and divide the two to get the capacity retention rate.
[0178] 2.45℃ high temperature cycle test:
[0179] At 45°C, charge at a constant current of 0.3C to 4.2V, charge at a constant voltage of 4.2V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 0.3C to 3.0V; repeat the charge and discharge steps for 400 cycles, test and record the discharge capacity of the 400th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0180] 3.55℃ high temperature 15 days storage test:
[0181] At 25°C, the battery was charged to 4.2V at a constant current of 0.3C, and then charged to a cut-off current of 0.05C at a constant voltage of 4.2V. The battery was then discharged to 3.0V at a constant current of 0.3C. The discharge capacity was recorded as C. 1 At 25°C, the battery was charged to 4.2V at a constant current of 0.3C, and charged to a cut-off current of 0.05C at a constant voltage of 4.2V. The battery was then transferred to 55°C and left for 15 days. The battery was then discharged to 3.0V at a constant current of 0.3C. The discharge capacity was recorded as C. 2 , 60℃ storage for 30 days capacity retention rate = C 2 / C 1 *100%.
[0182] 4. High temperature DCIR (abbreviation for “Direct Current Internal Resistance”) test:
[0183] The lithium-ion battery was charged at 25°C at a constant current of 0.3C to 4.2V, and at a constant voltage of 4.2V to a cut-off current of 0.05C. The battery was then discharged at a constant current of 0.3C for 30min. After standing for 1h, it was discharged at a constant current of 1.0C for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 1 The battery that has completed the 15-day storage test at 55°C was charged to 4.2V at 0.3C constant current at 25°C, and charged to a cut-off current of 0.05C at 4.2V constant voltage. The battery was then discharged at 0.3C constant current for 30 minutes. After being left for 1 hour, it was discharged at 1.0C constant current for 10 seconds. The DCIR of the battery at 50% SOC was calculated and recorded as D 2 Battery impedance change rate = D 2 / D 1 *100%.
[0184] 5. High temperature expansion test:
[0185] The lithium-ion battery is charged at 25°C at a constant current of 0.3C to 4.2V, and then at a constant voltage of 4.2V to a cut-off current of 0.05C. The initial thickness of the lithium-ion battery is measured and recorded as T 1 Then store at 55℃ for 15 days, test the thickness of lithium-ion battery at 55℃, and record the value as T 2 . Battery expansion rate (%) = (T 2 -T 1 ) / T 1 ×100%.
[0186]
Preparation and performance testing of sodium ion batteries
[0187] Embodiment 51
[0188] Preparation of electrolyte: The electrolyte is prepared with the following components according to mass fraction: 12.5% NaPF 6 , non-aqueous organic solvent 4-methyl-1,3-diepoxypentane is 35%, 1,2-dimethoxyethane is 21.5%, dimethyl carbonate is 30%, and the compound represented by formula 1-2 is 1.0%.
[0189] Preparation of positive electrode sheet: The positive electrode active material NaNi 1 / 3 Mn 1 / 3 Fe 1 / 3 O 2 Powder, conductive agent acetylene black, carbon nanotubes and binder polyvinylidene fluoride (PVDF) are dispersed in a solvent NMP in a mass ratio of 95:2:0.5:2.5 to obtain a positive electrode active material layer slurry; the positive electrode active material layer slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling, baking, slitting and spot welding of the pole ears.
[0190] Preparation of negative electrode sheet: Disperse the negative electrode active material hard carbon, conductive agent conductive carbon black super p, binder SBR, and dispersant CMC in deionized water at a mass ratio of 95:1.5:2:1.5, and stir evenly to obtain the negative electrode active material layer slurry; evenly coat the negative electrode active material layer slurry on the surface of the negative electrode current collector aluminum foil, and obtain the negative electrode sheet after drying, rolling, baking, slitting and spot welding the pole ears.
[0191] Diaphragm: 16μm three-layer PP ceramic diaphragm, with PP (polypropylene) as the substrate, and ceramic coatings applied on both sides of the substrate.
[0192] Preparation of the battery: stack the prepared positive electrode sheet, negative electrode sheet and 16μm three-layer separator in order, place the separator between the positive electrode sheet and the negative electrode sheet, flatten the wound body after winding and put it into an aluminum-plastic film packaging bag, and vacuum bake it at 75℃ for 48h to obtain the battery cell to be filled with liquid, and then inject the above-mentioned electrolyte into the battery cell in a glove box. After packaging, formation, aging and capacity separation, the preparation of the sodium ion battery is completed, and the designed capacity is 950mAh.
[0193] NeNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 -Test methods for sodium ion battery systems
[0194] 1.25℃ normal temperature cycle test:
[0195] At 25°C, charge at a constant current of 1.0C to 4.0V, charge at a constant voltage of 4.0V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.65V; repeat the charge and discharge steps for 1000 cycles, test and record the discharge capacity of the 700th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0196] 2.45℃ high temperature cycle test:
[0197] At 45°C, charge at a constant current of 1.0C to 4.0V, charge at a constant voltage of 4.0V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.65V; repeat the charge and discharge steps for 400 cycles, test and record the discharge capacity of the 400th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0198] 3.60℃ high temperature 15 days storage test:
[0199] At 25°C, the battery was charged to 4.0V at 1.0C constant current, charged to a cut-off current of 0.05C at 4.0V constant voltage, and then discharged to 2.65V at 1.0C constant current. The discharge capacity is recorded as C 1 At 25°C, the battery was charged to 4.0V at 1.0C constant current, and charged to a cut-off current of 0.05C at 4.0V constant voltage. The battery was then transferred to 60°C and left for 15 days. The battery was then discharged to 2.65V at 1.0C constant current. The discharge capacity was recorded as C. 2 , 60℃ storage for 15 days capacity retention rate = C 2 / C 1 *100%.
[0200] 4. High temperature DCIR (abbreviation for “Direct Current Internal Resistance”) test:
[0201] The lithium-ion battery was charged at 1.0C constant current to 4.0V at 25°C, and charged at 4.0V constant voltage to a cut-off current of 0.05C. The battery was then discharged at 1.0C constant current for 30min. After standing for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 1 The battery that has completed the 60℃ high temperature 15-day storage test was charged to 4.0V at 1.0C constant current at 25℃, and charged to a cut-off current of 0.05C at 4.0V constant voltage. The battery was then discharged at 1.0C constant current for 30min. After being left for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 2 Battery impedance change rate = D 2 / D 1 *100%.
[0202] 5. High temperature expansion test:
[0203] The lithium-ion battery was charged at 25°C at a constant current of 1.0C to 4.0V, and then at a constant voltage of 4.0V to a cut-off current of 0.05C. The initial thickness of the lithium-ion battery was measured and recorded as T 1 Then store at 60℃ for 15 days, test the thickness of lithium-ion battery at 60℃, and record the value as T 2 . Battery expansion rate (%) = (T 2 -T 1 ) / T 1 ×100%.
[0204] Embodiment 52
[0205] The battery was prepared by the method of Example 51, except that: in the preparation of the electrolyte, "NaClO 4 "Replace "NaPF 6 "; In the preparation of the positive electrode, "NaNi 0.4 Fe 0.2 Mn 0.4 O 2 " is replaced by "NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 ”.
[0206] NeNi 0.4 Fe 0.2 Mn 0.4 O 2 -Test methods for hard carbon battery systems
[0207] 1.25℃ normal temperature cycle test:
[0208] At 25°C, charge at a constant current of 1.0C to 4.05V, charge at a constant voltage of 4.05V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.65V; repeat the charge and discharge steps for 1000 cycles, test and record the discharge capacity of the 700th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0209] 2.45℃ high temperature cycle test:
[0210] At 45°C, charge at a constant current of 1.0C to 4.05V, charge at a constant voltage of 4.05V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C to 2.65V; repeat the charge and discharge steps for 400 cycles, test and record the discharge capacity of the 400th cycle and the 1st cycle, and divide the two to get the capacity retention rate.
[0211] 3.60℃ high temperature 15 days storage test:
[0212] At 25°C, the battery was charged to 4.05V at 1.0C constant current, charged to a cut-off current of 0.05C at 4.05V, and then discharged to 2.65V at 1.0C constant current. The discharge capacity is recorded as C 1 At 25°C, the battery was charged to 4.05V at a constant current of 1.0C, and charged to a cut-off current of 0.05C at a constant voltage of 4.05V. The battery was then transferred to 60°C and left for 15 days. The battery was then discharged to 2.65V at a constant current of 1.0C. The discharge capacity was recorded as C. 2 , 60℃ storage for 15 days capacity retention rate = C 2 / C 1 *100%.
[0213] 4. High temperature DCIR (abbreviation for “Direct Current Internal Resistance”) test:
[0214] The lithium-ion battery was charged at 1.0C constant current to 4.05V at 25°C, and charged at 4.05V constant voltage to a cut-off current of 0.05C. The battery was then discharged at 1.0C constant current for 30min. After standing for 1h, it was discharged at 2.0C constant current for 10s. The DCIR of the battery at 50% SOC was calculated and recorded as D 1 The battery that has completed the 15-day storage test at 60°C was charged to 4.05V at 1.0C constant current at 25°C, and charged to a cut-off current of 0.05C at a constant voltage of 4.05V. The battery was then discharged at 1.0C constant current for 30 minutes. After being left for 1 hour, it was discharged at 2.0C constant current for 10 seconds. The DCIR of the battery at 50% SOC was calculated and recorded as D 2 Battery impedance change rate = D 2 / D 1*100%.
[0215] 5. High temperature expansion test:
[0216] The lithium-ion battery was charged at 25°C at a constant current of 1.0C to 4.05V, and then at a constant voltage of 4.05V to a cut-off current of 0.05C. The initial thickness of the lithium-ion battery was measured and recorded as T 1 Then store at 60℃ for 15 days, test the thickness of lithium-ion battery at 60℃, and record the value as T 2 . Battery expansion rate (%) = (T 2 -T 1 ) / T 1 ×100%.
[0217] The methods provided in Examples 1-52, the components and their contents are shown in Tables 1-6.
[0218]
[0219]
[0220]
[0221]
[0222]
[0223]
[0224] 2. Test results
[0225] The performance test results are shown in Table 7 and Table 8.
[0226] Table 7
[0227]
[0228] Table 8
[0229]
[0230] Performance test conclusion: By comparing Examples 1-22 and Comparative Example 1, it can be determined that the addition of silicon-based fluorophosphate compounds can construct a high-conductivity, rigid, dense and stable interface film, which enables the lithium battery of the high-voltage system to exhibit excellent cycle stability and high temperature resistance; taking the compound of Formula 2 as an example, the application concentration range is studied, and it can be seen that the silicon-based fluorophosphate compound needs to be used within a suitable concentration range, otherwise the cycle performance and high-temperature storage stability of the battery will fluctuate greatly, and the battery performance cannot be stably improved; further, through experiments, the amount of the first solvent used, the type of the second solvent, the amount of the second solvent used, and the application of suitable formulas to different battery systems have a great impact on the impedance performance, capacity preservation and gas production of the battery. It is verified through experiments that within a suitable range, the performance improvement effect of the battery under high voltage has the best benefits.
[0231] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: It includes an additive, a first solvent and a second solvent; the additive includes a silicon-based fluorophosphate compound, and the silicon-based fluorophosphate compound is as shown in Formula 1: wherein R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl, and R1, R2 and R3 are the same or different from each other; The first solvent includes an ether compound; The second solvent includes at least one of a carbonate compound, a carboxylate compound, a sulfone compound and a nitrile compound.
2. The non-aqueous electrolyte according to claim 1, characterized in that The ether compound includes at least one of a chain ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms.
3. The non-aqueous electrolyte according to claim 2, characterized in that The chain ether compound having 3 to 10 carbon atoms includes at least one of ethyl ether, di(2,2,2-trifluoroethyl) ether, ethyl(2,2,2-trifluoroethyl) ether, ethyl n-propyl ether, ethyl(3-fluoro-n-propyl) ether, (2,2,2-trifluoroethyl)(3,3,3-trifluoro-n-propyl) ether, di(2,2,3,3,3-pentafluoro-n-propyl) ether, dimethoxymethane, methoxyethoxymethane, methoxy(2-fluoroethoxy)methane, diethoxymethane, ethoxy(2-fluoroethoxy)methane, (2,2,2-trifluoroethoxy)(1,1,2,2-tetrafluoroethoxy)ethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; And / or, the cyclic ether compound having 3 to 6 carbon atoms includes any one of tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane and 1,4-dioxolane.
4. The non-aqueous electrolyte according to claim 1, characterized in that The ether compounds include fluorine-substituted ether compounds.
5. The non-aqueous electrolyte according to claim 1, characterized in that The R4 and R5 independently include any one of F, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, and C2-C4 fluoroalkenyl.
6. The non-aqueous electrolyte according to claim 1, characterized in that The R1, R2, and R3 are each independently any one of a C1-C2 alkyl group and a C2-C3 alkenyl group; and / or, the R4 and R5 are each independently F or a methyl group.
7. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by Formula 1 includes at least one of the compounds represented by Formula 1-1 to Formula 1-22: Compound represented by formula 1-1 Compound represented by formula 1-2 Compounds shown in formula 1-3 Compounds shown in formula 1-4 Compounds shown in formula 1-5 Compounds shown in formula 1-6 Compounds shown in formula 1-7 Compound represented by formula 1-8 Compounds shown in formula 1-9 Compound represented by formula 1-10 Compound represented by formula 1-11 Compounds shown in formula 1-12 Compounds shown in formula 1-13 Compounds shown in formula 1-14 Compound represented by formula 1-15 Compound represented by formula 1-16 Compound represented by formula 1-17 Compound represented by formula 1-18 Compound represented by formula 1-19 Compounds shown in formula 1-20 Compound represented by formula 1-21 Compound represented by formula 1-22 8. The non-aqueous electrolyte according to claim 1, characterized in that At least one of the following is met: (i) the second solvent is a carbonate compound; (ii) the first solvent is a combination of a linear ether compound having 3 to 10 carbon atoms and a cyclic ether compound having 3 to 6 carbon atoms; (iii) The first solvent is a combination of a fluorine-substituted ether compound and a non-fluorine-substituted ether compound.
9. The non-aqueous electrolyte according to any one of claims 1 to 8, characterized in that: The non-aqueous electrolyte satisfies at least one of the following: (a) the mass percentage of the additive in the electrolyte is 0.05% to 5.0%; (b) the mass percentage of the first solvent in the electrolyte is 20% to 90%; (c) The mass percentage of the second solvent in the electrolyte is 3% to 70%.
10. The non-aqueous electrolyte according to claim 1, characterized in that The electrolyte salt further comprises a lithium salt or a sodium salt; the electrolyte salt satisfies at least one of the following: (a) The lithium salts include inorganic lithium salts and organic lithium salts; Optionally, the organic lithium salt includes at least one of carboxylic acid lithium salts, sulfonic acid lithium salts, imide lithium salts, methylated lithium salts, boric acid lithium salts, lithium oxalate salts and fluorinated ester sulfonic acid lithium salts; the inorganic lithium salt includes at least one of lithium hexafluorophosphate and lithium perchlorate; (b) the sodium salt comprises at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bis(oxalatoborate), sodium difluorophosphate, sodium difluorooxalatophosphate, sodium tetrafluorooxalatophosphate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; (b) The mass percentage of the electrolyte salt in the electrolyte is 6% to 30%.
11. A battery, characterized in that: A non-aqueous electrolyte comprising the non-aqueous electrolyte according to any one of claims 1 to 10.
12. The battery according to claim 11, characterized in that Includes sodium secondary batteries and lithium secondary batteries.
13. The battery according to claim 12, characterized in that The sodium secondary battery comprises a positive electrode sheet, a negative electrode sheet and a separator; and satisfies at least one of the following: (α) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer includes a positive electrode active material, wherein the positive electrode active material NaNi x Fe y M z O2, Na3V2(PO4)3, Na 0.9 Mn 0.6 Fe 0.4 At least one of PO4, sodium ferric pyrophosphate and sodium ferrocyanide; wherein M comprises one or more of Co, Mn, Fe and Cu, and x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1; (β) The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of sodium metal, soft carbon, hard carbon, sodium titanate, and sodium alloy; (γ) The diaphragm includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
14. The battery according to claim 12, characterized in that The lithium secondary battery comprises a positive electrode sheet, a negative electrode sheet and a separator; and satisfies at least one of the following: (a) The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4、Li2Mn 1-x O4, M is selected from one or more of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, F, 0≤a<0.2, 0≤x<1; (β) The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of metallic lithium, graphite, soft carbon, hard carbon, silicon, silicon oxide, silicon carbon composite and lithium titanate; (γ) The diaphragm includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene and polyethersulfone.
Citation Information
Patent Citations
Lithium ion secondary battery electrolyte and lithium ion secondary battery
CN108963339A
Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery
CN114402468A
Electrolyte and preparation method and application thereof
CN116247304A
Low-temperature electrolyte for lithium metal battery and application of low-temperature electrolyte
CN116598595A
High-temperature-resistant lithium ion battery electrolyte and lithium ion battery
CN117374403A
Cited By
Non-aqueous electrolyte and battery
WO2026114126A1